Organic-inorganic composite thermoelectric material and preparation method thereof
Patent Information
- Application Number
- CN202611157617.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
[0016]与现有技术相比,本发明的积极进步效果在于:
Smart Images

Figure CN123022108A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermoelectric materials technology, specifically to an organic-inorganic composite thermoelectric material and its preparation method. Background Technology
[0002] Thermoelectric conversion technology enables the direct conversion between thermal and electrical energy, and has significant application value in fields such as industrial waste heat recovery, wearable electronic power supply, and distributed energy systems. While traditional inorganic thermoelectric materials (such as Bi₂Te₃ and PbTe) possess high figures of merit (ZT), they generally suffer from bottlenecks such as raw material scarcity, high processing temperatures, brittleness, and poor flexibility, making them unsuitable for curved heat sources and miniaturized devices. On the other hand, conductive polymers such as polyaniline (PANI) and poly(3,4-ethylenedioxythiophene) (PEDOT) offer advantages such as light weight, good flexibility, low cost, and ease of processing, but their electrical conductivity and Seebeck coefficient often have an inverse relationship, and the means to control thermal conductivity are limited, resulting in generally low ZT values. Single organic systems are insufficient to meet practical application requirements.
[0003] To balance the high electrical transport properties of inorganic materials with the flexible processing advantages of organic materials, organic-inorganic composite thermoelectric materials have become a current research hotspot. However, existing composite systems still face serious challenges: on the one hand, the poor interfacial compatibility between inorganic fillers and organic matrices, with interfacial defects and barriers hindering carrier transport, not only fails to effectively improve conductivity but also introduces additional interfacial scattering and recombination centers; on the other hand, the random dispersion of inorganic fillers easily leads to excessively high percolation thresholds and network discontinuities, and lacks a screening mechanism for carrier energy distribution, making it difficult to achieve synergistic optimization of conductivity and Seebeck coefficient. In addition, existing composite films mostly rely on a single conductive polymer network, resulting in a single carrier hopping path and limited transport efficiency; at the same time, traditional composite strategies rarely utilize photothermal-thermoelectric coupling effects, failing to effectively convert the local temperature gradient generated by photothermal conversion into additional thermal voltage, resulting in a single dimension of energy utilization.
[0004] Therefore, how to construct efficient carrier injection channels through interfacial molecular bridging, build a dual conductive network to reduce the percolation threshold, and introduce a photothermal synergistic mechanism to overcome the existing thermoelectric performance bottlenecks has become a key technical problem that urgently needs to be solved in the field of organic-inorganic composite thermoelectric materials. Summary of the Invention
[0005] To overcome the above-mentioned shortcomings, the present invention aims to provide an organic-inorganic composite thermoelectric material and its preparation method. Through 3-mercaptopropionic acid molecular bridging, a tight chemically bonded interface is constructed between Co3O4 / ZnWO4, carbon nanotubes, and PANI, eliminating the interfacial barrier and promoting efficient cross-interfacial carrier injection. Carbon nanotubes and PEDOT NWs synergistically construct a three-dimensional interpenetrating dual network, providing in-plane long-range transport and inter-chain short-range hopping channels, respectively, significantly reducing the percolation threshold. The Co3O4 / ZnWO4 heterojunction generates an energy filtering effect through interfacial band bending, preferentially screening high-energy carriers to synergistically improve the Seebeck coefficient and conductivity. Simultaneously, the photothermal conversion of Co3O4 couples with the broad-spectrum absorption of carbon nanotubes, establishing a light-induced local temperature gradient to amplify the thermoelectric voltage output. CSA-m-cresol secondary doping synergistically induces PANI molecular chain extension to enhance polaron delocalization; LAA post-treatment synchronously regulates the redox balance of the dual network to optimize carrier concentration; multi-scale interface phonon scattering effectively suppresses lattice thermal conductivity; finally, through the synergistic mechanism of interface bridging-network interpenetration-photothermal drive, the film is endowed with excellent thermoelectric figure of merit, flexibility and photothermal-thermoelectric coupling characteristics, making it suitable for flexible thermoelectric devices and solar thermoelectric co-generation.
[0006] The present invention solves the above-mentioned technical problems through the following technical solution: This invention provides a method for preparing an organic-inorganic composite thermoelectric material, comprising the following steps: Step 1: Grind and mix carbon nanotubes, ZnWO4, Co3O4, PANI and camphor sulfonic acid to obtain thin film powder; Step 2: Mix N,N-dimethylformamide and m-cresol until homogeneous, then add the film powder and mix until homogeneous to obtain a PANI-doped dispersion; Step 3: PEDOT NWs are added to the PANI doped dispersion, and then subjected to ultrasonic treatment and stirring, followed by filtration and drying to obtain the composite film. Step 4: Add LAA to water and stir evenly, then add the composite film, heat and dry to obtain the organic-inorganic composite thermoelectric material.
[0007] A further improvement of this invention is that the preparation method of PANI includes the following steps: Step A1: Add ammonium persulfate to acid solution I, stir and heat to obtain APS dispersion; Step A2: Add aniline monomer and 3-mercaptopropionic acid to acid solution II, and then treat with ultrasound and stirring to obtain aniline dispersion; Step A3: Add the APS dispersion to the aniline dispersion and stir at low temperature to carry out the polymerization reaction to obtain the polymerization product; Step A4: Add the polymerization product to ammonia water, stir, and then wash and dry to obtain PANI.
[0008] A further improvement of the present invention is that, in step A1, acid solution I is a hydrochloric acid solution with a concentration of 1~1.5 mol / L, and the heating temperature is 40-50℃; In step A2, acid solution II is a hydrochloric acid solution with a concentration of 0.9~1.2 mol / L; In step A3, the low temperature is 0~5℃, and the stirring time is 8~12h; In step A4, the concentration of ammonia water is 0.4~0.8 mol / L, and the stirring time is 24~36 h.
[0009] A further improvement of the present invention is that the mass ratio of ammonium persulfate, aniline monomer and 3-mercaptopropionic acid in the raw materials of PANI is 5~8:2~4:0.5~1.5.
[0010] A further improvement of this invention is that the preparation method of PEDOT NWs includes the following steps: Step B1: Add sodium dodecyl sulfate and PVP to water and stir to obtain dispersion A; Step B2: Add ferric chloride to water, stir and heat, then add EDOT monomer and continue heating and stirring to obtain dispersion B; Step B3: Add dispersion B to dispersion A, stir and heat, then add methanol and dimethyl sulfoxide and stir. After washing and drying, PEDOT NWs are obtained.
[0011] A further improvement of the present invention is that the mass ratio of sodium dodecyl sulfate, ferric chloride, EDOT monomer, dimethyl sulfoxide, methanol and PVP in the raw materials of PEDOT NWs is 1~3:0.3~0.6:0.1~0.2:0.4~0.7:4~8:0.3~0.5.
[0012] A further improvement of the present invention is that, in step B2, the heating temperature is 50~70℃ and the heating time is 12~18h; In step B3, the heating temperature is 50~60℃, the heating time is 6~9h, and the concentration of dimethyl sulfoxide is 5%~10% by volume.
[0013] A further improvement of this invention is that the mass ratio of PANI to carbon nanotubes, ZnWO4, Co3O4 and camphor sulfonic acid is 1.5~2.5:1:0.1~0.3:0.5~0.9:0.4~0.8; The mass ratio of N,N-dimethylformamide, m-cresol, PEDOT NWs to PANI and LAA is 20~30:10~15:0.6~1.2:1.5~2.5:0.1~0.5.
[0014] A further improvement of the present invention is that, in step three, the frequency of ultrasonic treatment is 30kHz, and the filtration treatment uses an organic filter membrane with a pore size of 0.45μm; in step four, the temperature of heating treatment is 70~90℃, and the heating treatment time is 10~20min.
[0015] The present invention also provides an organic-inorganic composite thermoelectric material, which is prepared by the preparation method described above.
[0016] Compared with the prior art, the positive and progressive effects of the present invention are as follows: The organic-inorganic composite thermoelectric material prepared in this invention uses carbon nanotubes as a three-dimensional conductive framework, significantly improving the mechanical strength and in-plane conductivity of the thin film. The introduction of a photothermal semiconductor Co3O4 / ZnWO4 heterojunction utilizes the intrinsic photothermal conversion properties of Co3O4 to enhance heat transfer performance, and the energy filtering effect generated by the band bending at the heterojunction interface optimizes the synergistic relationship between the Seebeck coefficient and electrical conductivity. Simultaneously, PANI and PEDOT NWs construct a dual-conductive polymer network, forming a three-dimensional interpenetrating flow channel, reducing the carrier transition barrier. Secondary doping of PANI with m-cresol causes its molecular chains to transform from a coiled state to an extended state, enhancing conjugation and polaron delocalization, further improving electrical conductivity and thermoelectric potential.
[0017] The organic-inorganic composite thermoelectric material prepared in this invention incorporates 3-mercaptopropionic acid modification to improve the interfacial compatibility between the inorganic filler and the organic matrix, reducing interfacial defects and carrier traps. A multi-scale heterogeneous interface is formed between carbon nanotubes, Co3O4 / ZnWO4, and the polymer matrix, generating a strong phonon scattering effect that effectively suppresses lattice thermal conductivity. This results in improved electrical conductivity while maintaining low thermal conductivity, which is beneficial for obtaining a high thermoelectric figure of merit (ZT). LAA post-treatment precisely controls the redox states of PANI / PEDOT, optimizing carrier concentration and Fermi level positions. Ball milling-filtration processes achieve nanoscale uniform dispersion and in-plane oriented alignment, endowing the film with excellent flexibility and anisotropic transport properties. This material combines photothermal-thermoelectric coupling capabilities with the advantages of low-temperature solution processing, making it suitable for flexible thermoelectric devices, wearable energy harvesting, and solar-thermoelectric co-generation. Attached Figure Description
[0018] The accompanying drawings are provided to further understand the invention and constitute a part of this invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0019] Figure 1 This is a simplified diagram of the preparation method of the material of the present invention; Figure 2 Figure 1 shows the conductivity test results of the organic-inorganic composite thermoelectric materials prepared in the examples and comparative examples; Figure 3 Figure 1 shows the Seebeck coefficient test results of the organic-inorganic composite thermoelectric materials prepared in the examples and comparative examples; Figure 4 The graph shows the PF test results of the organic-inorganic composite thermoelectric materials prepared in the examples and comparative examples. Detailed Implementation
[0020] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0021] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0022] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0023] In this article, unless otherwise specified, “contains,” “includes,” “containing,” “has,” or similar terms cover the meanings of “composed of” and “mainly composed of,” for example, “A contains a” covers the meanings of “A contains a and others” and “A contains only a.”
[0024] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to specific examples. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention are within the scope of protection of the present invention.
[0026] The following examples use instruments and equipment conventional in the art. Experimental methods in the following examples, unless otherwise specified, are generally performed under standard conditions or as recommended by the manufacturer. All raw materials used in the following examples are conventional commercially available products with specifications in the art, unless otherwise stated.
[0027] See Figure 1 This invention provides a method for preparing an organic-inorganic composite thermoelectric material, specifically including the following steps: Step 1: Carbon nanotubes, ZnWO4, Co3O4, PANI, and camphor sulfonic acid are ground and mixed to obtain a thin film powder. This step, through mechanical grinding, achieves preliminary uniform dispersion of each solid component in the solid state, increases the contact area between the components, and lays the foundation for the subsequent formation of a uniform dispersion in the liquid phase.
[0028] Step 2: Mix N,N-dimethylformamide and m-cresol until homogeneous, then add the thin film powder obtained in Step 1 and mix until homogeneous to obtain a PANI-doped dispersion. N,N-dimethylformamide acts as a good solvent, while m-cresol serves as a dopant and auxiliary solvent for PANI. The solvent system formed by their mixture effectively dissolves and disperses the thin film powder, particularly promoting the full extension and doping of the PANI molecular chains in the solution.
[0029] Step 3: PEDOT NWs are added to the PANI doped dispersion obtained in Step 2. The mixture is then subjected to ultrasonic treatment and stirring, followed by filtration and drying to obtain a composite film. Ultrasonic treatment helps to further break up any potential nanofiller agglomerates and promotes the uniform dispersion of PEDOT NWs in the dispersion. Filtration rapidly deposits the solids in the dispersion into a film, which is then quickly separated by the solvent to form a dense composite film. Drying removes any residual solvent from the film. Thus, a conductive network synergistically constructed by carbon nanotubes and PEDOT NWs is formed within the PANI matrix.
[0030] Step 4: Add LAA to water and stir until homogeneous. Then add the composite film obtained in Step 3 to the mixture. After heat treatment and drying, the organic-inorganic composite thermoelectric material is obtained. LAA, as a reducing agent, can regulate the redox state of PANI and PEDOT in the composite film by heating its aqueous solution, thereby optimizing the final carrier concentration and transport characteristics and obtaining a high-performance composite thermoelectric material.
[0031] In a specific embodiment of the present invention, the method for preparing PANI is further defined. Optionally, the method for preparing PANI includes the following steps: Step A1: Add ammonium persulfate to acid solution I, stir and heat to obtain an APS dispersion. Ammonium persulfate acts as an oxidant, dissolving and pre-activating in an acidic environment to provide initiating species for subsequent aniline polymerization.
[0032] Step A2: Add aniline monomer and 3-mercaptopropionic acid to acid solution II, and then treat with ultrasound and stirring to obtain an aniline dispersion. The introduction of 3-mercaptopropionic acid is to participate in the reaction during the polymerization of aniline monomer, grafting the thiol functional group onto the PANI molecular chain or acting as a capping agent to improve the interfacial compatibility and chemical bonding between the final PANI and inorganic nanomaterials (such as carbon nanotubes, ZnWO4, Co3O4).
[0033] Step A3: Add the APS dispersion obtained in step A1 to the aniline dispersion obtained in step A2, and stir at low temperature to carry out the polymerization reaction to obtain the polymer product. Low temperature conditions are beneficial for controlling the polymerization rate, making the polymerization of aniline more regular and ordered, which helps to form PANI with longer molecular chains and higher degree of conjugation, while reducing the occurrence of side reactions.
[0034] Step A4: Add the polymerization product obtained in step A3 to ammonia water, stir, wash and dry to obtain PANI. Use ammonia water to remove doping from the intrinsic state of the polymerization product, converting it to the intrinsic state (or intermediate oxidation state). After washing and drying, pure PANI powder can be obtained.
[0035] In one embodiment of the present invention, the process parameters of the PANI preparation method can be further selected. Optionally, in step A1, acid solution I is a hydrochloric acid solution with a concentration of 1~1.5 mol / L, and the heating temperature is 40-50℃. In step A2, acid solution II is a hydrochloric acid solution with a concentration of 0.9~1.2 mol / L. In step A3, the low-temperature setting is 0~5℃, and the stirring time is 8~12 h. In step A4, the concentration of ammonia water is 0.4~0.8 mol / L, and the stirring time is 24~36 h.
[0036] Optionally, the mass ratio of the raw materials used in the above-mentioned PANI preparation process can also be optimized. In some embodiments, the mass ratio of ammonium persulfate, aniline monomer, and 3-mercaptopropionic acid is 5~8:2~4:0.5~1.5. By controlling the ratio of oxidant, monomer, and modifier, the molecular weight, yield, conductivity, and degree of reaction with 3-mercaptopropionic acid of PANI can be adjusted.
[0037] In one embodiment of the present invention, the method for preparing PEDOT NWs is further defined. Optionally, the method for preparing PEDOT NWs includes the following steps: Step B1: Add sodium dodecyl sulfate and PVP (polyvinylpyrrolidone) to water and stir to obtain dispersion A. Sodium dodecyl sulfate acts as a template agent or soft template, and PVP acts as a structure directing agent and stabilizer. Together, they form a micelle system in water, providing a confined space for the subsequent polymerization of EDOT monomers in one dimension.
[0038] Step B2: Add ferric chloride to water, stir and heat, then add EDOT monomer and continue heating and stirring to obtain dispersion B. Ferric chloride acts as an oxidant, forming an oxidizing solution in water. Heating promotes the oxidative polymerization reaction between ferric chloride and the subsequently added EDOT monomer.
[0039] Step B3: Add dispersion B obtained in step B2 to dispersion A obtained in step B1, stir and heat, then add methanol and dimethyl sulfoxide and stir. After washing and drying, PEDOT NWs are obtained. Introducing dispersion B containing the oxidant and monomer into the template agent system dispersion A confines the polymerization reaction of EDOT to the micelle interface, thereby growing into a one-dimensional nanowire structure. Methanol and dimethyl sulfoxide, as auxiliary solvents, can adjust the polarity of the system and the morphology of the micelles, which helps to obtain nanowires with uniform morphology.
[0040] In one embodiment of the present invention, the process parameters and raw material ratios of the PEDOT NWs preparation method can be further selected. Optionally, the mass ratio of sodium dodecyl sulfate, ferric chloride, EDOT monomer, dimethyl sulfoxide, methanol, and PVP is 1~3:0.3~0.6:0.1~0.2:0.4~0.7:4~8:0.3~0.5. With this ratio, PEDOT nanowires with uniform diameter and good dispersibility can be obtained. In some embodiments, in step B2, the heating temperature is 50~70°C, and the heating time is 12~18 h. In step B3, the heating temperature is 50~60°C, the heating time is 6~9 h, and the concentration of dimethyl sulfoxide is 5%~10% by volume.
[0041] In this embodiment, the formulation ratio of the final composite material and the process parameters of each step are further selected. Optionally, the mass ratio of PANI to carbon nanotubes, ZnWO4, Co3O4, and camphor sulfonic acid is 1.5~2.5:1:0.1~0.3:0.5~0.9:0.4~0.8. This ratio can balance the synergistic effect among the components. The mass ratio of N,N-dimethylformamide, m-cresol, PEDOT NWs to PANI and LAA is 20~30:10~15:0.6~1.2:1.5~2.5:0.1~0.5. By controlling the proportions of solvent, dopant, dual-network components, and post-treatment agents, the film-forming properties, conductive network construction, and final carrier concentration can be optimized.
[0042] In some embodiments, the ultrasonic treatment in step three is performed at a frequency of 30 kHz to effectively disperse the nanowires; the filtration process uses an organic filter membrane with a pore size of 0.45 μm to effectively retain the nanofiller and form a dense film. In step four, the heating treatment is performed at a temperature of 70–90 °C for 10–20 min to regulate the redox state of the film at a suitable rate.
[0043] Example 1 An organic-inorganic composite thermoelectric material comprises the following materials in parts by weight: 1.5 parts PANI, 0.4 parts camphor sulfonic acid, 20 parts DMF, 0.6 parts PEDOT NWs, 1 part carbon nanotubes, 0.1 parts ZnWO4, 0.5 parts Co3O4, 10 parts m-cresol, and 0.1 parts LAA.
[0044] Preparation of PEDOT NWs: S11. Weigh 1 part sodium dodecyl sulfate and 0.3 parts PVP and add them to 6 parts deionized water. Stir at 800 r / min for 30 min to obtain dispersion A. S12. Weigh 0.3 parts of ferric chloride and add it to 6 parts of deionized water. Stir at 800 r / min for 30 min and heat at 50℃ for 12 h. Weigh EDOT monomer and add it to the mixture. Continue stirring at the above speed and heat at the above temperature for 6 h to obtain dispersion B. S13. Add the dispersion B obtained in step S12 to the dispersion A obtained in step S11, stir at 800 r / min for 30 min, heat at 50℃ for 6-9 h, weigh out 4 parts of methanol and 0.4 parts of DMSO and add them, with the concentration of DMSO being 5% by volume. Continue stirring at the above speed for 2 h, wash with deionized water and anhydrous ethanol alternately 3 times each, and dry at 70℃ for 24 h to obtain PEDOT NWS.
[0045] Preparation of PANI: S21. Weigh 5 parts of ammonium persulfate and add them to 80-120 parts of acid solution I, where acid solution I is hydrochloric acid solution with a concentration of 1 mol / L. Stir at 500 r / min and heat at 40-50℃ for 2 h to obtain APS dispersion. S22. Weigh 2 parts of aniline monomer and 0.5 parts of 3-mercaptopropionic acid and add them to acid solution II, where acid solution II is a hydrochloric acid solution with a concentration of 0.9 mol / L. Sonicate at a frequency of 30 kHz for 20 min and stir at a speed of 500 r / min for 1 h to obtain an aniline dispersion. S23. Slowly add the APS dispersion obtained in step S21 to the aniline dispersion obtained in step S22, stir for 8 hours at a speed of 300 r / min, and polymerize at 0℃ to obtain the polymer product. S24. The polymerization product obtained in step S23 is added to 100 parts of ammonia water with a concentration of 0.4 mol / L. The mixture is stirred at 500 r / min for 24 h. The product is washed three times each with deionized water and anhydrous ethanol, and then dried at 70 °C for 24 h to obtain PANI.
[0046] Preparation of organic-inorganic composite thermoelectric materials: S31. Weigh 1 part carbon nanotubes, 0.1 part ZnWO4, 0.5 part Co3O4, 1.5 part PANI and 0.4 part camphor sulfonic acid, grind them in a ball mill for 30 minutes, and sieve them through a 200-mesh screen to obtain thin film powder. S32. Weigh 20 parts of DMF and 10-15 parts of m-cresol and mix them. Stir at 500 r / min for 30 min. Add the film powder obtained in step S31 and continue stirring at the above speed for 30 min to obtain PANI doped dispersion. S33. Weigh 0.6 parts of PEDOT NWs and add them to the PANI doped dispersion obtained in step S32. Sonicate at 30 kHz for 30 min, stir at 500 r / min for 30 min, filter using an organic -0.45 μm filter membrane, and dry at 70 °C for 24 h to obtain the composite film. S34. Weigh 0.1 parts of LAA and add it to 50 parts of deionized water. Stir for 10 minutes at a speed of 500 r / min. Add the composite film obtained in step S33 to the mixture and heat it at a temperature of 70°C for 10 minutes. Then dry it at a temperature of 70°C for 24 hours to obtain the organic-inorganic composite thermoelectric material.
[0047] Example 2 An organic-inorganic composite thermoelectric material comprises the following materials in parts by weight: 2 parts PANI, 0.6 parts camphor sulfonic acid, 25 parts DMF, 0.9 parts PEDOT NWs, 1 part carbon nanotubes, 0.2 parts ZnWO4, 0.7 parts Co3O4, 13 parts m-cresol, and 0.3 parts LAA.
[0048] Preparation of PEDOT NWs: S11. Weigh 2 parts sodium dodecyl sulfate and 0.4 parts PVP and add them to 8 parts deionized water. Stir at 800 r / min for 30 min to obtain dispersion A. S12. Weigh 0.5 parts of ferric chloride and add it to 8 parts of deionized water. Stir at 800 r / min for 30 min and heat at 60℃ for 15 h. Weigh EDOT monomer and add it to the mixture. Continue stirring at the above speed and heat at the above temperature for 8 h to obtain dispersion B. S13. Add the dispersion B obtained in step S12 to the dispersion A obtained in step S11, stir at 800 r / min for 30 min, heat at 55℃ for 6-9 h, weigh out 6 parts of methanol and 0.6 parts of DMSO and add them, the concentration of DMSO is 8% by volume, continue stirring at the above speed for 3 h, wash with deionized water and anhydrous ethanol alternately 3 times each, and dry at 70℃ for 24 h to obtain PEDOT NWS.
[0049] Preparation of PANI: S21. Weigh 7 parts of ammonium persulfate and add them to 100 parts of acid solution I, where acid solution I is a hydrochloric acid solution with a concentration of 1.3 mol / L. Stir at 500 r / min and heat at 45℃ for 3 h to obtain an APS dispersion. S22. Weigh 3 parts of aniline monomer and 1 part of 3-mercaptopropionic acid and add them to acid solution II. Acid solution II is a hydrochloric acid solution with a concentration of 1.1 mol / L. Sonicate at a frequency of 30 kHz for 20 min and stir at a speed of 500 r / min for 2 h to obtain an aniline dispersion. S23. Slowly add the APS dispersion obtained in step S21 to the aniline dispersion obtained in step S22, stir for 10 hours at a speed of 300 r / min, and polymerize at a low temperature of 3℃ to obtain the polymer product. S24. The polymer obtained in step S23 is added to 100 parts of ammonia water with a concentration of 0.6 mol / L. The mixture is stirred at 500 r / min for 30 h. The product is washed three times each with deionized water and anhydrous ethanol, and then dried at 70 °C for 24 h to obtain PANI.
[0050] Preparation of organic-inorganic composite thermoelectric materials: S31. Weigh 1 part carbon nanotubes, 0.2 parts ZnWO4, 0.7 parts Co3O4, 2 parts PANI and 0.6 parts camphor sulfonic acid, grind them in a ball mill for 30 minutes, and sieve them through a 200-mesh screen to obtain thin film powder; S32. Weigh 25 parts DMF and 13 parts m-cresol and mix them. Stir at 500 r / min for 40 min. Add the film powder obtained in step S31 and continue stirring at the above speed for 30 min to obtain PANI doped dispersion. S33. Weigh 0.9 parts of PEDOT NWs and add them to the PANI doped dispersion obtained in step S32. Sonicate at 30 kHz for 30 min, stir at 500 r / min for 30 min, filter using an organic -0.45 μm filter membrane, and dry at 70 °C for 24 h to obtain the composite film. S34. Weigh 0.3 parts of LAA and add it to 50 parts of deionized water. Stir for 10 minutes at a speed of 500 r / min. Add the composite film obtained in step S33 to the mixture and heat it at 80℃ for 15 minutes. Then dry it at 80℃ for 24 hours to obtain the organic-inorganic composite thermoelectric material.
[0051] Example 3 An organic-inorganic composite thermoelectric material comprises the following materials in parts by weight: 2.5 parts PANI, 0.8 parts camphor sulfonic acid, 30 parts DMF, 1.2 parts PEDOT NWs, 1 part carbon nanotubes, 0.3 parts ZnWO4, 0.9 parts Co3O4, 15 parts m-cresol, and 0.5 parts LAA.
[0052] Preparation of PEDOT NWs: S11. Weigh 3 parts sodium dodecyl sulfate and 0.5 parts PVP and add them to 9 parts deionized water. Stir at 800 r / min for 30 min to obtain dispersion A. S12. Weigh 0.6 parts of ferric chloride and add it to 9 parts of deionized water. Stir at 800 r / min for 30 min and heat at 70℃ for 18 h. Weigh EDOT monomer and add it to the mixture. Continue stirring at the above speed and heat at the above temperature for 9 h to obtain dispersion B. S13. Add the dispersion B obtained in step S12 to the dispersion A obtained in step S11, stir at 800 r / min for 30 min, heat at 50-60℃ for 9 h, weigh out 8 parts of methanol and 0.7 parts of DMSO and add them, with the concentration of DMSO being 10% by volume, continue stirring at the above speed for 4 h, wash with deionized water and anhydrous ethanol alternately 3 times each, and dry at 70℃ for 24 h to obtain PEDOTNWS.
[0053] Preparation of PANI: S21. Weigh 8 parts of ammonium persulfate and add them to 120 parts of acid solution I, where acid solution I is hydrochloric acid solution with a concentration of 1.5 mol / L. Stir at 500 r / min and heat at 50℃ for 4 h to obtain APS dispersion. S22. Weigh 4 parts of aniline monomer and 1.5 parts of 3-mercaptopropionic acid and add them to acid solution II, which is a hydrochloric acid solution with a concentration of 1.2 mol / L. Sonicate at 30 kHz for 20 min and stir at 500 r / min for 1-3 h to obtain an aniline dispersion. S23. Slowly add the APS dispersion obtained in step S21 to the aniline dispersion obtained in step S22, stir for 12 hours at a speed of 300 r / min, and polymerize at a low temperature of 0-5℃ to obtain the polymer product. S24. The polymerization product obtained in step S23 is added to 100 parts of ammonia water with a concentration of 0.8 mol / L. The mixture is stirred at 500 r / min for 36 h. The product is then washed three times each with deionized water and anhydrous ethanol, and dried at 70 °C for 24 h to obtain PANI.
[0054] Preparation of organic-inorganic composite thermoelectric materials: S31. Weigh 1 part carbon nanotubes, 0.3 parts ZnWO4, 0.9 parts Co3O4, 2.5 parts PANI and 0.8 parts camphor sulfonic acid, grind them in a ball mill for 30 minutes, and sieve them through a 200-mesh screen to obtain thin film powder. S32. Weigh 30 parts of DMF and 15 parts of m-cresol and mix them. Stir at 500 r / min for 50 min. Add the film powder obtained in step S31 and continue stirring at the above speed for 30 min to obtain PANI doped dispersion. S33. Weigh 1.2 parts of PEDOT NWs and add them to the PANI doped dispersion obtained in step S32. Sonicate at 30 kHz for 30 min, stir at 500 r / min for 30 min, filter using an organic -0.45 μm filter membrane, and dry at 70 °C for 24 h to obtain the composite film. S34. Weigh 0.5 parts of LAA and add it to 50 parts of deionized water. Stir for 10 minutes at a speed of 500 r / min. Add the composite film obtained in step S33 to the mixture and heat it at a temperature of 90°C for 20 minutes. Then dry it at a temperature of 90°C for 24 hours to obtain the organic-inorganic composite thermoelectric material.
[0055] To verify the technical effects of the present invention, the following comparative examples were provided: Comparative Example 1: Compared to Example 2, the carbon nanotube component was removed, but the remaining raw material ratios and preparation processes were completely identical; Comparative Example 2: Compared to Example 2, the ZnWO4 component was removed, while all other conditions remained the same; Comparative Example 3: Compared to Example 2, the Co3O4 component was removed, while the other conditions remained the same.
[0056] The properties of the materials prepared in the above embodiments and comparative examples were tested: Figure 2 The results show the conductivity test results of the composite thermoelectric materials in different embodiments and comparative examples. Figure 2It can be seen that the electrical conductivity of Examples 1-3 is 1048.6 S / cm, 1126.1 S / cm, and 1015.5 S / cm, respectively. Among them, Example 2 has the highest electrical conductivity, indicating that the appropriate proportions of PANI, PEDOT nanowires, carbon nanotubes, and inorganic components are beneficial to the formation of continuous and stable charge carrier transport channels. After removing carbon nanotubes from Comparative Example 1, the electrical conductivity decreased to 888.8 S / cm, the lowest among all groups of samples, indicating that carbon nanotubes play an important role in connecting conductive polymers and constructing long-range conductive networks. After removing ZnWO4 and Co3O4 from Comparative Examples 2 and 3, respectively, the electrical conductivity increased to 1198.7 S / cm and 1152.3 S / cm, respectively, indicating that the interface formed by inorganic components may have a certain scattering or hindering effect on charge carrier migration. However, the increase in electrical conductivity does not necessarily mean a simultaneous increase in the overall thermoelectric performance of the material.
[0057] Figure 3 The Seebeck coefficient test results are for the composite thermoelectric materials in different embodiments and comparative examples. Figure 3 It can be seen that Example 2 has the highest Seebeck coefficient at 24.62 μV / K, followed by Example 3 at 23.05 μV / K, indicating that a suitable organic-inorganic component ratio is beneficial for controlling the energy distribution and transport behavior of charge carriers. After removing ZnWO4 and Co3O4 from Comparative Examples 2 and 3, respectively, the Seebeck coefficients decreased to 18.90 μV / K and 19.70 μV / K, indicating that the heterostructure formed by ZnWO4 and Co3O4 has a positive effect on improving the Seebeck coefficient. It may suppress some low-energy charge carriers through interface scattering or energy filtering effects, thereby increasing the thermoelectric potential generated per unit temperature difference.
[0058] Figure 4 The power factor test results are for the composite thermoelectric materials in different embodiments and comparative examples. According to PF=S 2 Based on σ calculations, the power factors for Examples 1-3 are approximately 45.45, 68.26, and 53.95 μW·m, respectively. -1 ·K -2 Example 2 showed the highest power factor, indicating that the formulation achieved a good balance between conductivity and Seebeck coefficient. The power factors of Comparative Examples 1, 2, and 3 were approximately 44.60, 42.82, and 44.72 μW·m, respectively. -1 ·K -2 The values were all lower than in Example 2. This shows that carbon nanotubes are mainly used to construct continuous conductive networks, while ZnWO4 and Co3O4 mainly regulate carrier transport through the organic-inorganic interface. The synergistic effect between the components can balance the material's electrical conductivity and thermoelectric potential output capability, thereby improving the power factor and electrothermal performance of the composite thermoelectric material.
[0059] Finally, it should be noted that the embodiments listed above are merely one or more specific manifestations of the technical solution of this invention. Their purpose is to clearly illustrate the concept, principle, and application of this invention through specific examples, and is by no means intended to limit the scope of protection of this invention to these specific embodiments. In fact, the true value of this invention lies in its proposed technical ideas and innovations, rather than its manifestations or implementation methods.
[0060] For those skilled in the art, after thoroughly reading and understanding the technical solution of this invention, they are fully capable of making various changes, modifications, or equivalent substitutions to the specific implementation of the invention based on their own professional knowledge and skills. These changes may include, but are not limited to: adjusting the range of technical parameters, optimizing the algorithm flow to improve efficiency, and replacing some technical components to achieve better compatibility or reduce costs. As long as these modified technical solutions substantially retain the technical features claimed by the original invention, that is, they can still achieve the core functions and effects of this invention, then these changes should be considered to fall within the scope of protection of the pending claims of this invention.
[0061] Furthermore, with the continuous progress and development of technology, new technical means and methods are constantly emerging, which provides ample space for further improvement and perfection of this invention. Therefore, the scope of protection of this invention should also include reasonable and foresightful improvements and extensions based on existing technology. As long as these improvements and extensions do not depart from the basic principles and core concepts of this invention, they should be considered equivalents of this invention and are equally protected by patent rights.
Claims
1. A method for preparing an organic-inorganic composite thermoelectric material, characterized in that, Includes the following steps: Step 1: Grind and mix carbon nanotubes, ZnWO4, Co3O4, PANI and camphor sulfonic acid to obtain thin film powder; Step 2: Mix N,N-dimethylformamide and m-cresol until homogeneous, then add the film powder and mix until homogeneous to obtain a PANI-doped dispersion; Step 3: PEDOT NWs are added to the PANI doped dispersion, and then subjected to ultrasonic treatment and stirring, followed by filtration and drying to obtain the composite film. Step 4: Add LAA to water and stir evenly, then add the composite film, heat and dry to obtain the organic-inorganic composite thermoelectric material.
2. The method for preparing the organic-inorganic composite thermoelectric material according to claim 1, characterized in that, The preparation method of PANI includes the following steps: Step A1: Add ammonium persulfate to acid solution I, stir and heat to obtain APS dispersion; Step A2: Add aniline monomer and 3-mercaptopropionic acid to acid solution II, and then treat with ultrasound and stirring to obtain aniline dispersion; Step A3: Add the APS dispersion to the aniline dispersion and stir at low temperature to carry out the polymerization reaction to obtain the polymerization product; Step A4: Add the polymerization product to ammonia water, stir, and then wash and dry to obtain PANI.
3. The method for preparing the organic-inorganic composite thermoelectric material according to claim 2, characterized in that, In step A1, acid solution I is a hydrochloric acid solution with a concentration of 1~1.5 mol / L, and the heating temperature is 40-50℃; In step A2, acid solution II is a hydrochloric acid solution with a concentration of 0.9~1.2 mol / L; In step A3, the low temperature is 0~5℃, and the stirring time is 8~12h; In step A4, the concentration of ammonia water is 0.4~0.8 mol / L, and the stirring time is 24~36 h.
4. The method for preparing the organic-inorganic composite thermoelectric material according to claim 2, characterized in that, In PANI's raw materials, the mass ratio of ammonium persulfate, aniline monomer, and 3-mercaptopropionic acid is 5~8:2~4:0.5~1.
5.
5. The method for preparing the organic-inorganic composite thermoelectric material according to claim 1, characterized in that, The preparation method of PEDOTNWs includes the following steps: Step B1: Add sodium dodecyl sulfate and PVP to water and stir to obtain dispersion A; Step B2: Add ferric chloride to water, stir and heat, then add EDOT monomer and continue heating and stirring to obtain dispersion B; Step B3: Add dispersion B to dispersion A, stir and heat, then add methanol and dimethyl sulfoxide and stir. After washing and drying, PEDOT NWs are obtained.
6. The method for preparing the organic-inorganic composite thermoelectric material according to claim 5, characterized in that, In the raw materials of PEDOTNWs, the mass ratio of sodium dodecyl sulfate, ferric chloride, EDOT monomer, dimethyl sulfoxide, methanol and PVP is 1~3:0.3~0.6:0.1~0.2:0.4~0.7:4~8:0.3~0.
5.
7. The method for preparing the organic-inorganic composite thermoelectric material according to claim 5, characterized in that, In step B2, the heating temperature is 50~70℃, and the heating time is 12~18h; In step B3, the heating temperature is 50~60℃, the heating time is 6~9h, and the concentration of dimethyl sulfoxide is 5%~10% by volume.
8. The method for preparing the organic-inorganic composite thermoelectric material according to claim 1, characterized in that, The mass ratio of PANI to carbon nanotubes, ZnWO4, Co3O4 and camphor sulfonic acid is 1.5~2.5:1:0.1~0.3:0.5~0.9:0.4~0.8; The mass ratio of N,N-dimethylformamide, m-cresol, PEDOT NWs to PANI and LAA is 20~30:10~15:0.6~1.2:1.5~2.5:0.1~0.
5.
9. The method for preparing the organic-inorganic composite thermoelectric material according to claim 1, characterized in that, In step three, the ultrasonic treatment frequency is 30kHz, and the filtration treatment uses an organic filter membrane with a pore size of 0.45μm; in step four, the heating treatment temperature is 70~90℃, and the heating treatment time is 10~20min.
10. An organic-inorganic composite thermoelectric material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 9.
